Development of Personalized Health Messages to Promote Engagement in Advance Care Planning. Issue 2 (25th January 2016) - Fried, Terri R.; Redding, Colleen A.; Robbins, Mark L.; Paiva, Andrea L.; O'Leary, John R.; Iannone, Lynne
Abstract : Objectives: To develop and test the acceptability of personalized intervention materials to promote advance care planning (ACP) based on the Transtheoretical Model (TTM), in which readiness to change is a critical organizing construct. Design: Development study creating an expert system delivering TTM‐personalized feedback reports and stage‐matched brochures with more‐general information on ACP and modifications based on participant reviews. Setting: Senior centers. Participants: Community‐living persons aged 65 and older (N = 77). Measurements: Participant ratings of length, attractiveness, and trustworthiness of and reactions to reports and brochures. Results: The expert system assessed participants' readiness to engage in each of four ACP behaviors: completion of a living will, naming a health care proxy, communication with loved ones about quality vs quantity of life, and communication with clinicians about quality vs quantity of life. The system also assessed pros and cons of engagement and values and beliefs that influence engagement. The system provided individualized feedback based on the assessment, with brochures providing additional general information. Initial participant review indicating unacceptable length led to revision of feedback reports from full‐sentence paragraph format to bulleted format. After review, the majority of participants rated the materials as easy to read, trustworthy, providing new information, making them more comfortable reading about ACP, and increasing interest in participating in ACP. Conclusion: Older adults found an expert system individualized feedback report and accompanying brochure to promote ACP engagement to highly acceptable and engaging. Additional research is necessary to examine the effects of these materials on behavior change.